DEVELOPING SOCIAL CAPITAL WITHIN COMPANIES THROUGH ENTERPRISE 2.0 - Virtanen, Kustaa (My University, 2013)
Whereas external social media has been studied, hyped and integrated into companies´ strategies, an insignificant concentration has been put on internal social solutions, which companies provide increasingly to their personnel. An enterprise focusing solely on the benefits of external social media might end up underestimating the true potential embedded in social business. The purpose of this thesis was to examine how social collaboration can be depicted as a structuration process in an Enterprise 2.0 environment. Furthermore, this thesis sought to reveal the benefits, challenges and possibilities of social business. This thesis focused on researching Enterprise 2.0 at the workplace. The studied Enterprise 2.0 solution was IBM Connections. The qualitative research methodology was an extensive case study. Three companies took part into this thesis and all in all 12 employees were interviewed. Additionally, seven IBM Social Business Experts were interviewed in order to receive a better understanding of the phenomenon. Three research questions were designed to fulfill the purpose of this thesis. The research questions were: 1. How are the dimensions of social capital structured through collaboration? 2. How does agency form in Enterprise 2.0? 3. How does social collaboration emerge as a result of the interplay between agency and dimensions of social capital in an Enterprise 2.0 environment and creates outcomes such as trust, identification and knowledge? The main research findings indicate that social collaboration increases trust, identification and knowledge by giving employees more capabilities to do their work. Consequently, social collaboration increases company performance by making individuals and groups more effective. The support of top management is crucial in making Enterprise 2.0 successful, because it is more a cultural than a technological change. Power agency, the lack of top management support and old established work ways such as email and databases work as barriers to social collaboration.